The Visual Arts of Masjid Agung Sang Cipta Rasa Cirebon: Hybrid Culture Identity (Department of Drama, Dance and Music, FBS, Universitas Negeri Semarang, 2020)
Cultural hybrids complement the richness of the visual art of Masjid Agung Sang Cipta Rasa in Cirebon. The influence of diversity can be seen in the mosque including having strong local cultural characteristics, coupled with the influence of foreign cultures such as Arabic, India, and China. This study aims to find hybrid culture crosses in elements of Masjid Agung Sang Cipta Cipta. The method used is the historical method. The historical method is the process of critically testing and analyzing records and relics of the past. This method consists of several stages, namely heuristics, criticism, interpretation, and historiography. The results of this study describe various forms of hybridity that have influenced the development of Masjid Agung Sang Cipta Rasa. The elements are considered to represent the period before Islam entered, or the influence of Hindu Buddhism, Chinese, Arab, Javanese, and European that coexist in Cirebon. The elements of visual arts in the mosque which are part of the hybrid cultural cross-identity among which are represented on the roof that gets influence (Javanese, Hindu-Buddhist, Arabic/Islamic); gate (Hindu-Buddhist); maksurah (Arabic); mihrab (Arabic, Chinese); pillars (Javanese, Arabic). This shows that the greatest influence on the building of Masjid Agung Sang Cipta Rasa, starting from the earliest development until several centuries later, is the influence of culture from outside.